2022
DOI: 10.1021/acsaem.2c03301
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Surface Coating and Oxygen Vacancy Dual Strategy Endowing a Li-Rich Li1.2Mn0.55Ni0.11Co0.14O2 Cathode with Superior Lithium Storage Performance

Abstract: Lithium-rich Mn-based cathode materials are widely regarded as the next-generation cathode materials for high-energy-density lithium-ion batteries owing to their low cost and high specific capacity. Nonetheless, their commercial application is seriously hindered by low initial Coulombic efficiency, capacity loss, and voltage drop during long-term cycling. Herein, surface phosphorus doping and a mixture protective layer with oxygen vacancies (OVs) which consists of Li 3 PO 4 and LiMnPO 4 as a surfacecoating lay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…The adjacent splits at (006)/(012) and (018)/(110) of all of the samples indicate a well-layered structure. The c/a ratio and cation mixing degree of Li + /Ni 2+ are two main factors used widely to estimate the LMR layered structure. We have calculated them using Jade software (see Table S1) and concluded that even the LMR-MS2 sample exhibits some slight Li + /Ni 2+ mixing degree. This might have unfavorable effects on lithium-ion diffusion.…”
Section: Resultsmentioning
confidence: 99%
“…The adjacent splits at (006)/(012) and (018)/(110) of all of the samples indicate a well-layered structure. The c/a ratio and cation mixing degree of Li + /Ni 2+ are two main factors used widely to estimate the LMR layered structure. We have calculated them using Jade software (see Table S1) and concluded that even the LMR-MS2 sample exhibits some slight Li + /Ni 2+ mixing degree. This might have unfavorable effects on lithium-ion diffusion.…”
Section: Resultsmentioning
confidence: 99%
“…[ 1 ] Among potential cathode materials for LIBs, Ni‐rich layered oxide ternary cathode materials are the most promising due to their excellent overall properties, such as high‐energy‐density, good cycling performance, and moderate cost. [ 2,3 ] As reported, the energy density of Ni‐rich layered oxides materials can be further improved by increasing the Ni content and the upper cut‐off voltage. However, the structure of the Ni‐rich layered oxides material becomes unstable under high voltage, which prevents the full utilization of its lithium storage capacity.…”
Section: Introductionmentioning
confidence: 95%
“…The energy crisis and environmental pollution make the development of large-scale energy storage systems imminent. Lithium-ion batteries (LIBs) dominate the energy storage field of 3C electronics and the electric vehicle industry [1][2][3][4]. Nevertheless, the limited resources of lithium, safety, and high cost dramatically hinder the future sustainability of lithium-ion batteries [5][6][7].…”
Section: Introductionmentioning
confidence: 99%